A marketing paradigm for successful lean implementation. (13th February 2009) - Sawhney, Rapinder; Lee, Tzong-Ru; Wu, Hsiao-Chen; Chen, Shiou-Yu
Since the early 1990s, many companies have begun adopting lean principles and practices. While it appears to be an effective methodology to improve operational efficiency and process productivity, lean implementation has failed in many organisations with their performance sliding back to the original state. This situation is due to a number of reasons, one of which being, the poor marketing of lean to people. This article proposes a conceptual design for marketing Lean, with 'Planning for change' acting as a prerequisite. This new paradigm aims to sustain lean successfully in the organisation.